The international classification of functioning, disability and health in clinical practice, research findings and their impact on training and education - Liane Simon; Liane Simon; Friederike Gölz; Olaf Schenk; Olaf Schenk; Thorsten Bührmann; Thorsten Bührmann; Mathias Kauff; Mathias Kauff; Olaf Kraus de Camargo; Stefanus Snyman; George Lüers; et al. (Frontiers Media S.A., 2024)
At the ICF Research Institute (at MSH Medical School Hamburg) multiprofessional experts collaborate on various research projects with a focus on bio-psycho-social health and education. Initially, the main goal was monitoring and evaluating the implementation of the International Classification of Functioning, Disability and Health (ICF) in clinical practice. Over time and based on the initial findings, the research group started developing new approaches to support training and education of health professionals in the use of the ICF. As a result, substantial changes have recently been made in the curriculum and structure of several courses to improve and expand interprofessional teaching at the MSH Medical School Hamburg (MSH). Furthermore, creative didactic approaches in combination with interprofessional education have been developed.